Inhibitory Activity of Levofloxacin against MDR Staphylococcus aureus and Pseudomonas aeruginosa Clinical Isolates - Lisa Nathalie; Lindawati Alimsardjono; Isnaeni Isnaeni (Universitas Airlangga, 2019)
Introduction: Staphylococcus aureus and Pseudomonas aeruginosa are the most dangerous and important species among their genus. These bacteria are often resistant to many classes of antimicrobial agents; which make difficulties in selecting appropriate drug to treat infections. Multidrug-resistance occurs readily in hospitals for which antimicrobials agents were used widely. Objective: The aims of this study was to determine minimum inhibitory concentration (MIC) and minimum bacterial concentration (MBC) of levofloxacin against 22 multidrug resistant- clinical (MDR) strains of Staphylococcus aureus and Pseudomonas aeruginosa isolated from patients pus and urine in hospital. Methods: Determination of the MIC was performed by macro-dilution broth assay as recommended by Clinical and Laboratory Standards Institute (CLSI), while the MBC was determined one-step further after the MIC determination. Results: It was found that MIC of the levofloxacin were (0.3 ± 0.0) - >0.5 µg/mL and (0.2 ± 0.1) - (1.0 ±0.0)µg/mL against S. aureus from pus and urine, respectively. In addition, higher MICs were yielded against P. aeruginosa, (1.0 ± 0.0) - >8.0 µg/mL and (0.7 ± 0.3) - (3.0 ± 1.2) µg/mL for pus and urine isolates respectively. Similar to MICs, the MBCs against P. aeruginosa were higher than S. aureus, (0.6 ± 0.0) - > 4.0 µg/mL and (0.3 ± 0.0) - >8.0 µg/mL isolated from pus and urine respectively, (2.0 ± 0.6) - > 8.0 µg/mL and (3.0 ± 1.2) - >7.0 µg/mL against P. aeruginosa from pus and urine respectively. Conclusion: The levofloxacin was still susceptible as bacteriostatic against isolates from both body fluids, but not bactericidal towards all isolates.